Which nasopharyngeal cancer patients need adaptive radiotherapy? - Yu-Chang Hu; Kuo-Wang Tsai; Ching-Chih Lee; Nan-Jing Peng; Ju-Chun Chien; Hsin-Hui Tseng; Po-Chun Chen; Jin-Ching Lin; Wen-Shan Liu (BMC Cancer, 2018)
Abstract Background Adaptive radiotherapy (ART) has potential benefits in patients with nasopharyngeal cancer (NPC). This retrospective study aimed to identify the factors favoring ART. Materials and methods Forty NPC patients were retrospectively included in this study. All patients received two-phase, volumetric modulated arc radiotherapy (VMAT) and underwent a second computed tomography (CT) for the phase II ART. We generated phantom, non-ART plans by a hybrid method for comparison with ART plans. A paired t-test was used to evaluate the dose differences between these two plans. A subgroup analysis through a paired t-test was used to evaluate the factors favoring ART. Results The second CT images were captured at the median 22 fractions. The median total dose of the planning target volume-one (PTV-1) was 72 Gy, and the phase II dose was 16 Gy. The volumes of the ipsilateral parotid gland (23.2 vs. 19.2 ml, p <  0.000), contralateral parotid gland (23.0 vs. 18.4 ml, p <  0.000), clinical target volume-1 (CTV-1, 32.2 vs. 20.9 ml, p <  0.000), and PTV-1 (125.8 vs. 107.3 ml, p <  0.000) all shrunk significantly between these two CT simulation procedures. Among the nearby critical organs, only the ipsilateral parotid gland displayed significant dose reduction by the ART plan (5.3 vs. 6.0 Gy, p = 0.004). Compared to the phantom plan, the ART could significantly improve the PTV-1 target volume coverage of D98 (15.4 vs. 12.3 Gy, p < 0.000). Based on the D98 of PTV-1, the factors of a large initial weight (> 60 kg, p < 0.000), large body mass index (BMI) (> 21.5, p < 0.000), obvious weight loss (> 2.8 kg, p < 0.000), concurrent chemoradiotherapy (p < 0.000), and stages III–IV (p < 0.000) favored the use of ART. Conclusions ART could significantly reduce the mean dose to the ipsilateral parotid gland. ART has dosimetrical benefit for patients with a heavy initial weight, large BMI, obvious weight loss, concurrent chemoradiotherapy, and cancer in stages III–IV.